Efficacy and safety of i.v. methylprednisolone pulse therapy for vitiligo: A retrospective study of 58 therapy experiences for 33 vitiligo patients. Issue 7 (25th March 2021) - Wada‐Irimada, Moyuka; Tsuchiyama, Kenichiro; Sasaki, Rui; Hatchome, Naokazu; Watabe, Akiko; Kimura, Yutaka; Yamasaki, Kenshi; Aiba, Setsuya
Abstract: Systemic corticosteroid is indicated for vitiligo, especially for generalized and progressive vitiligo. However, no consensus exists yet for the dosages and modalities of systemic corticosteroid treatments for vitiligo. The purpose of this study is to validate the efficacy and safety of i.v. methylprednisolone pulse therapy (IVMP) for patients with progressive generalized vitiligo. We retrospectively reviewed the medical records of vitiligo patients treated in our institute for 10 years between January 2010 and December 2019. Among 525 vitiligo patients treated in 10 years, 33 vitiligo patients (aged, 8–78 years; 18 female and 15 males) received IVMP, a single course of daily 500 mg methylprednisolone application (8 mg/kg/day for children) for 3 consecutive days. We observed that 14 of 25 (56%) achieved stable condition without lesion progression, and 12 of 19 (63%) had more than 25% repigmentation at 6 months after IVMP. A group of Vitiligo Area Scoring Index over 10 included more patients with Vitiligo Disease Activity Score of +3 and +4 disease progression at 6 months after the IVMP. We did not observe any severe adverse events relating to the IVMP procedures. In conclusion, IVMP is a safe and effective treatment for progressive generalized vitiligo.